Alojamiento de bajo impacto ambiental en la Patagonia Argentina - Schlüfer, Regina G. (Revista Turismo em Análise, 1995)
The article analyzes different environmental impact lodging emerged with the spread of ecotourism. Finally, refers to tourism in Argentinean Patagonia analyzing some kind of lodges appeared during last decade aiming to satisfy those tourists who search a closer contact with nature.